A gramatiquinha de Mário de Andrade: uma leitura historiográfica - Silva, Sandra Alves da (2007)
This project has as a theme the historiographical reading study of Mário de Andrade s Gramatiquinha . Being inserted in the research camp of Description and History of Portuguese Language , and presented as a result of previous researches performed at the Institute of Linguistics Researches Sedes Sapietiae for Portuguese Studies, specifically at the Portuguese Language Historiographical Researches Group. It is based on the theoretical-methodological principles of Konrad Koerner and directed by the following research questions on: 1) In what amount does Mário de Andrade s pronouns approach distances itself from Said Ali s grammar? 2) To what point Mário de Andrade s considerations in Gramatiquinha were used on the letters, on the theoretical texts from the aforementioned author? 3) What aspects of Celso Cunha s pronominal placement differ from Mário de Andrade s or Said Ali s? 4) What reflections could be made about pronouns placement in Brazilian spoken language during the 20 s? Based on the casted research question the objectives are presented: 1) Investigate the pronouns approach under Mário de Andrade s optics, during the 20 s; 2) Compare the pronoun explanations postulated on Said Ali s "Gramática Secundária" and its approach with Mário de Andrade s pronominal placement, related to Brazilian spoken language; 3) Identify Celso Cunha s opinion, concerning pronominal placement, taking as a comparative standard Mário de Andrade s suggested posture. The analysis are based on the following categories: a) Brazilianess aspects; b) grammatical-linguistic aspects of pronominal approach resulting in a posture outlining in relation to the use of pronouns agreeing with Brazilian spoken language, it is, the writer considers that Portuguese language speakers in Brazil should formulate their own rules, once nobody misplaces pronouns, everybody, simply uses them, and there are also those who follow grammatical rules only in formal situations. This posture differs from the ones postulated by Said Ali and Celso Cunha, because Mário de Andrade attained himself to the Brazilians colloquial use for his descriptions, unwilling to write a normative grammar directed to the cult norm grammatical standards